Stress and vibration analysis of a bicycle frame by finite element analysis - Hedry Q Amani Rizal Numeiry (Nanyang Technological University, 2022)
Bicycles are a staple of transport in the world. There have been many analyses done on bicycles to measure their yield stress and behaviour under loading. However, there has yet to be one done for a specified user whose weight is distributed onto different components based on positioning on the bicycle. This project aims to perform a stress and vibration analysis on the bicycle frame by finite element analysis based upon the boundary conditions of 3 cases: Case 1: seated and holding handlebars, Case 2: seated without holding the handlebar and Case 3: Standing and holding handlebars. The simulation software, APDL Mechanical Student Version (APDL), is used to create a 3D BEAM188 element model of a bicycle and simulate it based on the conditions of these 3 cases. From this, the displacement vector sum, Von Mises stress and mode shapes are found. By comparative analysis of the results, the weakest component can be evaluated. From this study, it was found that the Fork Joint had one of the highest displacements of 1.79mm, 1.43mm and 2.97mm for Case 1, Case 2 and Case 3 respectively. The component also displayed the highest Von Mises stress values of 0.132GPa, 0.11GPa and 0.202GPa for Case 1, Case 2 and Case 3 respectively. Lastly, the mode shapes of highest occurrences involve the Forked Joint. It was concluded that the Fork Joint was the weakest component in the bicycle frame.